2008
DOI: 10.1016/j.ymgme.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

1H MRS identifies symptomatic and asymptomatic subjects with partial ornithine transcarbamylase deficiency

Abstract: Objective To evaluate brain metabolism in subjects with partial ornithine transcarbamylase deficiency (OTCD) utilizing 1H MRS. Methods Single voxel 1H MRS was performed on 25 medically-stable adults with partial OTCD, and 22 similarly aged controls. Metabolite concentrations from frontal and parietal white matter (FWM, PWM), frontal gray matter (FGM), posterior cingulate gray matter (PCGM), and thalamus (tha) were compared with controls and IQ, plasma ammonia, glutamine, and disease severity. Results Cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 39 publications
2
54
0
Order By: Relevance
“…Hyperammonemia-related neurological injuries range from lethal cerebral edema to mild or subclinical cognitive impairment, depending on the severity of the defect (Gropman et al 2008), with the most severely affected patients typically presenting early in life (Brusilow and Maestri 1996;Summar et al 2008;Tuchman et al 2008). Ornithine transcarbamylase (OTC) deficiency is the most common UCD, accounting for slightly more than half of all UCD cases (Summar et al 2008;Tuchman et al 2008;Batshaw et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperammonemia-related neurological injuries range from lethal cerebral edema to mild or subclinical cognitive impairment, depending on the severity of the defect (Gropman et al 2008), with the most severely affected patients typically presenting early in life (Brusilow and Maestri 1996;Summar et al 2008;Tuchman et al 2008). Ornithine transcarbamylase (OTC) deficiency is the most common UCD, accounting for slightly more than half of all UCD cases (Summar et al 2008;Tuchman et al 2008;Batshaw et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, decreased brain Cr content was reported, in one patient with ASS, by Choi and Yoo (2001). On the contrary, other authors found normal cerebral Cr content in patients with OTC deficiency (Choi and Yoo 2001;Takanashi et al 2002;Gropman et al 2008), but it should be taken into account that probably H 1 -NMR brain spectroscopy is not the best method to show slight Cr decreases. Arginase deficiency (MIM#207800) is one of the most infrequent UCD; biochemically, this disease is characterized by hyperargininemia.…”
Section: Aslmentioning
confidence: 85%
“…In older children, peak ammonia levels are generally lower but remains >200 mmol/ L in most of the patients during acute crises (Enns et al 2007). However, severe neurological crises have been reported even in the absence of severe hyperammonemia (Kojic et al 2005;Mak et al 2007;Gropman et al 2008). This apparent discrepancy between neurological impairment and plasma ammonia level may be explained in part by the mechanisms of hyperammonemia neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved using an analysis program such as "LCModel," but this step needs most of the time the assistance of a specialist. The use and the accuracy of this method have been clearly validated to evaluate brain metabolism in OTCD patients (see Gropman et al 2008) for details), but this investigation cannot be regularly repeated (Connelly et al 1993). In contrast, continuous ICP monitoring was very useful to detect ICP peaks and to treat them immediately, in the aim to maintain adequate CPP and to prevent cerebral damages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation